Light and pH dual‐sensitive biodegradable polymeric nanoparticles for controlled release of cargos. Issue 10 (26th February 2017) - Xia, Yingchun; Zeng, Yunxiong; Hu, Ding; Shen, Huihui; Deng, Jianru; Lu, Yanbing; Xia, Xinnian; Xu, Weijian
ABSTRACT: In this article, a light and pH dual‐sensitive block copolymer PEG‐ b ‐poly(MPC‐Azo/DEA) was facilely prepared for the first time by azide‐alkyne click chemistry between amphiphilic block copolymer bearing pendant alkynyl group poly(ethylene glycol)‐poly(5‐methyl‐5‐propargylxycarbonyl‐1, 3‐dioxane‐2‐one) (PEG‐ b ‐poly(MPC)) and two azide‐containing compounds azobenzene derivative (Azo‐N3 ) and 2‐azido‐1‐ethyl‐diethylamine (DEA‐N3 ). Light response of the polymeric nanoparticles benefits from the azobenzene segments and pH responsiveness is attributed to DEA moieties. The prepared copolymer could self‐assemble into spherical micelle particles. The morphological changes of these particles in response to dual stimuli were investigated by UV/vis spectroscopy, dynamic light scattering (DLS), and transmission electron microscopy (TEM). Nile Red (NR) was utilized as probe, and fluorescence spectroscopy was served as an evidence for the enhanced release of cargos from polymeric nanoparticles under combined stimulation. Anticancer drug, DOX was loaded into the nanoparticles and the loaded‐DOX could be released from these nanoparticles under dual stimuli. MTT assays further demonstrated that PEG‐ b ‐poly(MPC) and PEG‐ b ‐poly(MPC‐Azo/DEA) were of biocompatibility and low toxicity against HepG2 cells as well as SMCC‐7721 cells. More importantly, the prepared DOX‐loaded nanoparticles exhibited good anticancer ability for the two cells. The synthesized light and pH dual‐sensitive biodegradable polymeric nanoparticles were expected to be platforms for precisely controlled release of encapsulated molecules. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1773–1783 Abstract : Light and pH sensitive PEG‐ b ‐poly(MPC‐Azo/DEA) were synthesized via ROP of cyclic carbonate bearing pendant alkynyl group followed by azide‐alkyne cycloaddition click reaction with azide‐containing compounds Azo‐N3 or DEA‐N3 . The morphological changes of the polymer micelles in response to dual stimuli were investigated. The release efficiency of loaded NR was greatly enhanced by the combined stimuli. Then DOX was loaded into the nanoparticles and the loaded‐DOX was released from these nanoparticles under dual stimuli. The obtained PEG‐ b ‐poly(MPC) and PEG‐ b ‐poly(MPC‐Azo/DEA) showed good biocompatibility and low toxicity against HepG2 cells as well as SMCC‐7721 cells. More importantly, the DOX‐loaded nanoparticles exhibited good anticancer ability for the two cells.